Find the quotient.
42j4k2 ÷ (-3j3k)

Question

Asked 11/4/2014 12:58:34 PM

Updated 11/4/2014 6:04:53 PM

5 Answers/Comments

This conversation has been flagged as incorrect.

s

drsyed19|Points 491|

eturker|Points 3077|

andrewpallarca|Points 45280|

= 5x^3 - 5x^2 + 2x^2 - 2x - 3x + 3

= 5x^3 - 3x^2 - 5x + 3

Question

Asked 11/4/2014 12:58:34 PM

Updated 11/4/2014 6:04:53 PM

5 Answers/Comments

This conversation has been flagged as incorrect.

Rating

5

360t + 10t^3 - 120t^2

= 10t(36 + t^2 - 12t)

= 10t(t - 6)^2

= 10t(t - 6)(t - 6)

= 10t(36 + t^2 - 12t)

= 10t(t - 6)^2

= 10t(t - 6)(t - 6)

Added 11/4/2014 6:00:54 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:38:25 AM]

5

(n + 8)(n - 2)

= n^2 + 8n - 2n - 16

= n^2 + 6n - 16

= n^2 + 8n - 2n - 16

= n^2 + 6n - 16

Added 11/4/2014 6:02:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:42:24 AM]

5

-7p^3(4p^2 + 3p - 1)

= -28p^5 - 21p^4 + 7p^3

= -28p^5 - 21p^4 + 7p^3

Added 11/4/2014 6:04:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:43:22 AM]

Factor this expression completely and then place the factors in the proper location on the grid. ab + 2a + 3b + 6 **Weegy:** (a+3)(b+2) **User:** Factor this expression completely and then place the factors in the proper location on the grid. ab + 4 + a + 4b **Weegy:** (a+3)(b+2) **User:** Factor this expression completely and then place the factors in the proper location on the grid.mn - 4m - 5n + 20 **Weegy:** mn - 4m - 5n + 20
= (m-5) (n-4) **User:** Factor this expression completely and then place the factors in the proper location on the grid. mr + ns - nr - ms **Weegy:** mr - ms - nr + ns
m(r - s) - n(r - s)
(m - n)(r - s) (More)

Question

Updated 10/30/2014 7:22:41 AM

1 Answer/Comment

Factor 5k 2 - 35k 3. **Weegy:** (a)5k^2(1 - 7k) is the answer. 5k^2(1 - 7k) = 5k^2 - 35k^3 **User:** Factor x 4 y 2 + x 3 y 3. **Weegy:** x+y=k is an equation of a straight line.
**User:** Factor 16p 4 - 24p 3. **Weegy:** 16p^4 - 24p^3 = 8p^3(2p - 3) **User:** Factor a 2 bc + ab 2 c + abc 2. **Weegy:** Can you clarify the equation please? **User:** Factor 10x 3 + 8x 2 - 6x. **User:** Factor 4n 4 + n 3. **Weegy:** (b)n^3(4n + 1) is the answer. (b)n^3(4n + 1) = 4n^4 + n^3 **User:** Factor -3x - 3y - 3z.
**Weegy:** The answer is -3(x + y + z) **User:** Factor 3y2 - 4y. **User:** -24a 3 b 3 c 3 - 84a 4 b 2 c factored equals -12a3b2c(2bc2 + 7a). **User:** What is the missing expression?
x 8 + 3x 5 = x5(_____)
**User:** Factor -4d 3 + 28d 2 - 4d. **Weegy:** -4d^3 + 28d^2 - 4d, the factors are -4d(d^2-7d+1). **User:** Factor 2a 5 b + 2a 4 b 2 + 2a 3 b 3. **User:** Factor 30y 2 z + 12yz 2 - 18yz. **Weegy:** 30y^2 z + 12yz^2 - 18yz, when factored is: 6yz(5y+2z-3) **User:** Factor 14a - 7b. **Weegy:** 14a - 7b can be factorized as 7(2a - b). **User:** Factor 48m - 80n. **Weegy:** 48m - 80n
gcd of 48 and 80 is 16
gcd of m and n is 1
gcd of terms is 16
= 16(3m ? 5n) (More)

Question

Updated 10/30/2014 3:01:02 AM

3 Answers/Comments

x^4y^2 + x^3y^3

= x^3y^2(x + y )

= x^3y^2(x + y )

Added 10/30/2014 2:44:18 AM

This answer has been confirmed as correct and helpful.

a^2bc + ab^2c + abc^2

= abc ( a + b + c )

= abc ( a + b + c )

Added 10/30/2014 2:45:20 AM

This answer has been confirmed as correct and helpful.

48m - 80n

= 16(3m - 5n)

= 16(3m - 5n)

Added 10/30/2014 3:00:21 AM

This answer has been confirmed as correct and helpful.

Factor n 3 - n 2 + 3n - 3. **Weegy:** 5 = 3N - 1 N = 2 **User:** Factor z 3 - 2z 2 + 9z - 18. **Weegy:** (z - 12)(z + 12) = z^2 + 12z - 12z - 144; = z^2 - 144 **User:** Factor y 2 + 10z - 10y - yz. **User:** Factor x 2 + xy - 2x - 2y. **User:** Factor ab + bc + b 2 + ac. **User:** Factor jm + jn + km + kn. **Weegy:** Factor jm + jn + km + kn.
j(m + n) + k(m + n) is (j + k)(m + n)
(More)

Question

Updated 10/30/2014 2:40:27 AM

3 Answers/Comments

n^3 - n^2 + 3n - 3

= n^2(n - 1) + 3(n - 1)

= (n - 1)(n^2 + 3)

= n^2(n - 1) + 3(n - 1)

= (n - 1)(n^2 + 3)

Added 10/30/2014 2:38:00 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [10/30/2014 8:52:00 AM]

z^3 - 2z^2 + 9z - 18

= z^2(z - 2) + 9(z - 2)

= (z - 2)(z^2 + 9)

= z^2(z - 2) + 9(z - 2)

= (z - 2)(z^2 + 9)

Added 10/30/2014 2:39:03 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [10/30/2014 8:53:04 AM]

What is the middle term of the product of (5a - 7)(2a - 1)? **Weegy:** (5a - 7)(2a - 1) = 10a^2 - 5a - 14a + 7; = 10a^2 - 19a + 9; The middle term is: -19a **User:** Factor 5x 2 - 7x + 2. **User:** Factor 2x 2 + 7x + 3. **User:** Find the length and width of a rectangle with an area of 2x 2 + x - 3. **Weegy:** 8x^2 - 2x = 1; 8x^2 - 2x - 1= 0; (4x + 1)(2x - 1) = 0 (4x + 1) = 0; 4x = -1, x = -1/4 or (2x - 1) = 0; 2x = 1; x = 1/2 Solution set: {x = -1/4, x = 1/2} **User:** What is the product of (4x + 3)(-2x - 5)? (More)

Question

Updated 11/1/2014 4:13:34 AM

4 Answers/Comments

5x^2 - 7x + 2

= 5x^2 - 2x - 5x + 2

= (5x - 2)(x - 1)

= 5x^2 - 2x - 5x + 2

= (5x - 2)(x - 1)

Added 11/1/2014 4:07:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:38:05 AM], Rated good by andrewpallarca

2x^2 + 7x + 3

= 2x^2 + x + 6x + 3

= (2x + 1)(x + 3)

= 2x^2 + x + 6x + 3

= (2x + 1)(x + 3)

Added 11/1/2014 4:08:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:39:21 AM], Rated good by andrewpallarca

The length and width of a rectangle with an area of 2x^2 + x - 3 is 2x + 3 and x - 1 .

2x^2 + x - 3

= (2x + 3)(x - 1)

2x + 3 is the length ,x - 1 is the width

2x^2 + x - 3

= (2x + 3)(x - 1)

2x + 3 is the length ,x - 1 is the width

Added 11/1/2014 4:11:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:39:47 AM], Rated good by andrewpallarca

(4x + 3)(-2x - 5)

= 4x*(-2x ) - 2x*3 + 4x*(-5) + 3*(-5)

= -8x^2 - 6x - 20x - 15

= -8x^2 - 26x - 15

= 4x*(-2x ) - 2x*3 + 4x*(-5) + 3*(-5)

= -8x^2 - 6x - 20x - 15

= -8x^2 - 26x - 15

Added 11/1/2014 4:13:34 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:40:39 AM], Rated good by andrewpallarca

34,880,827

questions answered

There are no comments.